Arctic Wolf Attacks Scientist -- A Unique Canadian Incident - Jenness, Stuart E. (ARCTIC, 1985)
Recent biological studies have concluded that North American wolves are rarely dangerous to humans. To date the scientific literature contains only one well-documented account of a vicious wolf attack on a man, an incident that took place in northwestern Ontario in 1942. A much earlier attack, however, took place in February 1915 on the Coppermine River in Canada's Arctic. Though mentioned in two publications in the 1920s, this incident has escaped the scientists' notice and is reported again now with additional information. In this encounter a large white wolf (Canis lupus mackenzii Anderson) entered the campsite of members of the 1913-18 Canadian Arctic Expedition and on discovery attacked one of the scientists. The incident is unique for three reasons: (1) the existence and reliability of eyewitness accounts of the attack in the unpublished diaries of two of the scientific members, one of whom was the wolf's victim; (2) the chance coincidence that the man who shot the wolf was a mammalogist responsible for collecting arctic specimens for the National Museum of Canada in Ottawa; and (3) the existence today, 70 years later, of the wolf mount in the museum's research collection.Key words: Arctic, wolf, Rudolph Anderson, Diamond Jenness, Frits Johansen, Canadian Arctic Expedition Mots clés: Arctique, loup, Rudolph Anderson, Diamond Jenness, Frits Johansen, expédition arctique canadienne